Predictors of sleepiness in obstructive sleep apnoea at baseline and after 6 months of continuous positive airway pressure therapy - Budhiraja, Rohit; Kushida, Clete A; Nichols, Deborah A; Walsh, James K; Simon, Richard D; Gottlieb, Daniel J; Quan, Stuart F (The European respiratory journal, 2017)
We evaluated factors associated with subjective and objective sleepiness at baseline and after 6 months of continuous positive airway pressure (CPAP) therapy in patients with obstructive sleep apnoea (OSA).We analysed data from the Apnoea Positive Pressure Long-term Efficacy Study (APPLES), a prospective 6-month multicentre randomised controlled trial with 1105 subjects with OSA, 558 of who were randomised to active CPAP. Epworth sleepiness scale (ESS) scores and the mean sleep latency (MSL) on the maintenance of wakefulness test at baseline and after 6 months of CPAP therapy were recorded.Excessive sleepiness (ESS score >10) was present in 543 (49.1%) participants. Younger age, presence of depression and higher apnoea-hypopnoea index were all associated with higher ESS scores and lower MSL. Randomisation to the CPAP group was associated with lower odds of sleepiness at 6 months. The prevalence of sleepiness was significantly lower in those using CPAP >4 h·night using CPAP ≤4 h·night Among those with good CPAP adherence, those with ESS >10 at baseline had significantly higher odds (OR 8.2, p<0.001) of persistent subjective sleepiness.Lower average nightly CPAP use and presence of sleepiness at baseline were independently associated with excessive subjective and objective sleepiness after 6 months of CPAP therapy.